Factors influencing the implementation of data analytics in South Africa - Rooplahl, Ramesh (My University, 2015)
The study explores the factors influencing South African businesses to implement data analytics to gain a competitive advantage. This was accomplished by a qualitative research method based on semi-structured, in-depth interviews with identified proponents of analytics in South Africa. Businesses today store vast quantities of data that are obtained from the day to day operations of the company. Organisations have realised that exploring this raw data utilising data science and statistics, can aid the business in formulating new strategies or disproving existing ones, thereby giving them a competitive advantage, at the same time. In the current economic and competitive climate, businesses require the ability to make fast, effective and accurate decisions to gain an advantage over their rivals. These decisions are made at all levels of business, including strategic and operational and have to address how customers wish to do business and their priorities and preferences are. Companies have increasingly started to use analytics on existing business data to understand their customers better and make offerings that are more relevant and customised to suit each customer individually, in a timely manner. The results of the research indicate that organisations that wish to use data analytics to differentiate themselves, in their respective industries, need to be mindful of certain factors that impact their effectiveness at being an analytics competitor. The study has also uncovered that South African companies that have implemented data analytics tend to follow similar thinking to international analytics leaders, when adopting data driven decision making.
Keywords: Information technology -- Management. Data mining.Decision making ;Strategic planning -- South Africa.